Non-English Students Motivation and Strategies in Learning English - Wardani Dwi Wihastyanang; M Fajar (Universitas PGRI Madiun, 2025)
The aims of this study is to provide insight into the motivation of non-English students at various levels, which can be used as a reference for our knowledge of the elements that influence non-English students' interest and motivation in learning English courses. Non-English students often have different goals and do not prioritize learning English in the same way as English students, who are more likely to have strong motivation and a methodical approach to learning the language. By looking at these issues, this study hopes to find information that can be used to modify English language teaching strategies to better suit their needs and improve language learning outcomes. This study uses quantitative, involving systematic data collection and analysis to measure the level of motivation among Non-English language students used in learning their English language courses. This quantitative research method includes questionnaires to collect data, followed by statistical analysis to draw conclusions and make inferences about the variables studied. From the results was founded that internal factors indicate that many students prioritize English proficiency for both academic and professional objectives, establish goals, and feel confident in their ability to improve. Their intrinsic motivation is also influenced by their enjoyment of English learning activities, such as practicing and completing assignments, demonstrating a favorable relationship between learning methodologies and personal objectives in English acquisition. Then, external factors, the data shows that students' enthusiasm to learn English is greatly increased by external variables including peer support, efficient teaching strategies, and readily available resources. Important components include group activities, exposure to English-language media, and instructor feedback. Peer and learning environment help further boost motivation, demonstrating a direct correlation between using successful learning tactics to increase English proficiency and outside assistance.